Cultural Representation and Ethnocentrism in Nollywood: Directorial Agency, Authenticity, and Globalization in Southern Nigerian Cinema - Vitalis, Perpetua Ogechi; Amadi, Richard N.; White, Dike Harcourt (Unisia, 2024)
This study investigates how Nollywood, Nigeria’s dynamic film industry, constructs and negotiates cultural identity and ethnocentrism within Southern Nigerian cinema. Anchored in Auteur Theory, Reflective–Projective Theory, and Cultivation Theory, it explores directors’ roles as cultural authors whose creative decisions shape perceptions of authenticity, morality, and national identity. Employing a qualitative, interpretive design and content analysis of secondary data, the research examines films and scholarly works that reflect Nollywood’s evolving socio-cultural narratives. Findings reveal that while Nollywood often reproduces ethnocentric and patriarchal ideologies through recurrent tropes, it simultaneously acts as a medium for cultural preservation, resistance, and dialogue. Directors emerge as mediators between tradition and modernity, balancing local authenticity with global market pressures intensified by digital technologies and transnational streaming platforms. Furthermore, the study identifies an emerging feminist consciousness among female filmmakers who challenge entrenched gender hierarchies. These dynamics underscore Nollywood’s dual character as both a cultural mirror and a transformative force capable of redefining African modernity and soft power. The research contributes to understanding the intersection of authorship, globalization, and representation in African cinema and highlights Nollywood’s potential to promote inclusive narratives and intercultural understanding while reinforcing Nigeria’s role as a leading voice in global cultural production.